Apostasy and Its Legal Consequences in Indonesian Personal Status Law: Human Rights Analysis and Doctrinal Tensions - Badrian Badrian (Jurnal Syariah dan Hukum Komparatif, 2026)
This study examines the legal implications of apostasy in Indonesia within the framework of Islamic personal status law, focusing on marriage dissolution, inheritance disqualification, and guardianship rights. Although apostasy is not criminalized under Indonesian national law, its consequences are civilly enforced through the Kompilasi Hukum Islam (KHI) and adjudicated by the Religious Courts. Drawing on classical Islamic jurisprudence, the legal system treats apostasy as a disqualifying condition that voids marital bonds, excludes individuals from inheriting from Muslim relatives, and impairs their capacity to act as guardians over Muslim children. The study employs a normative legal approach, supplemented by doctrinal analysis and relevant case studies, to assess how these civil sanctions affect individual rights. It further analyzes the tensions between doctrinal fidelity and Indonesia’s constitutional guarantees of religious freedom and non-discrimination. The findings reveal that civil consequences for apostasy, while doctrinally grounded, conflict with international human rights standards and potentially infringe upon constitutional protections. The study concludes that legal reform is necessary to harmonize religious law with human rights obligations, calling for a contextualized interpretation of Islamic principles that upholds justice, dignity, and individual liberty within Indonesia’s plural legal system.